2019
DOI: 10.1007/s40506-019-00200-w
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Overcome Implementation Challenges of Infection Prevention and Control in Low-Middle Income Countries

Abstract: Purpose of review Healthcare-associated infections (HAIs) and rising antimicrobial resistance (AMR) have posed a major challenge in patient care across the globe, more so in lower-middle-income countries (LMICs). Studies have shown that implementation of an effective infection prevention and control (IPC) program reduces incidence of HAI to a large extent. However, implementation of such a program in low-resource setting has many challenges. Research have shown that gaps exist due to absence of political will,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Cleaners have often been neglected in IPC programmes—data from 56 health facilities across Zanzibar, The Gambia, Bangladesh and India found that less than half provided any form of IPC training for cleaners and that the cleaning workforce had low status and poor work conditions [ 39 ]. In our study, the need for locally adapted training materials that are tailored to cleaning staff with low literacy was evident, which is a priority recognised more broadly for IPC training in low-resource settings [ 12 ], and something that is being piloted through initiatives such as TEACH CLEAN [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleaners have often been neglected in IPC programmes—data from 56 health facilities across Zanzibar, The Gambia, Bangladesh and India found that less than half provided any form of IPC training for cleaners and that the cleaning workforce had low status and poor work conditions [ 39 ]. In our study, the need for locally adapted training materials that are tailored to cleaning staff with low literacy was evident, which is a priority recognised more broadly for IPC training in low-resource settings [ 12 ], and something that is being piloted through initiatives such as TEACH CLEAN [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Challenges posed by staff shortages can be further hampered by a lack of IPC training for personnel and poor compliance with IPC practices, such as hand hygiene [ 9 16 ]. Overcrowding [ 9 12 , 15 ] and inadequate infection surveillance systems [ 10 , 11 , 13 , 14 , 16 ] have also been documented as key constraints to effective IPC in low resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare Associated Infections (HAIs) are a global health challenge for patient safety, and are a major driver of antimicrobial resistance (AMR) [1], particularly in lowerand middle-income countries (LMICs) [2]. Studies in Ethiopia and Nigeria have reported HAI cumulative incidences in surgical wards of between 5.7% and 45.8% [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability to conduct studies to address the disparities which prevent effective IPC programs, especially in low- and middle-income countries (LMICs), has been affected by a number of factors. These include limited or restricted resources, lack of training in IPC, lack of computer infrastructure to allow for appropriate surveillance, and multiple competing political agendas [ 85 ]. From the perspective of animal health, poor IPC at the level of animal health clinics have also been shown to cause environmental contamination, with resultant colonization transmitting from animals to humans in that environment [ 86 ].…”
Section: Antimicrobial Resistance Is Ancientmentioning
confidence: 99%